The theorodokoi inscription from Nemea (SEG 36, 331) and the date of IG IV, 583 - Xydopoulos, Ioannis (Tekmeria, 2017)
The Argives honored Nicocreon, king of Salamis in Cyprus, by dedicating a statue in the sanctuary of Hera. A well-known epigram (IG IV, 583) was inscribed on the base of the statue, where one could read that Nicocreon, son of Pnytagoras, was king in Cyprus, and that the Argives set up his statue “on account of the bronze which I was sending to the festival of Hera as prizes for the young men”. Although different dates have been suggested for the epigram, scholars have not reached a conclusion. Nicocreon was making donations to the Heraia while he was king, and the language of the epigram, as stated, suggests that he was doing so over a period of several years. Therefore, the date of the inscription should lie between a few years after 332/1 BC, year of Nicocreon’s ascension to the throne, to not long after his death in 311/0 BC. In this paper, an attempt is made to define the political circumstances both in Cyprus and in mainland Greece, to provide persuasive arguments that the epigram should be dated to the year 315 BC.